Production of Sorghum Seed and Straw Biomass for Feed as Affected by Different Harvesting Ages - Nazla Iftikhar; Panca Dewi Manu Hara Karti; Nur Rochmah Kumalasari; Luki Abdullah; Amalia, Ghina Tazkia (Journal of Tropical Crop Science, 2024)
This study evaluated the sorghum “Samurai Two” production for feed harvested at different times after planting during the rainy season. A randomized block design was employed with five groups and five treatments representing different harvesting ages: 90, 95, 100, 105, and 110 days after planting. The variables measured included panicle length, weight, dry weight, seed dry weight per panicle, 1000-seed weight, number of seeds, dry seed production, total fresh and dry weight of panicles, moisture content, and total fresh and dry weight of straw biomass. Harvesting between 90 and 100 DAP resulted in a higher fresh and dry panicle weight, fresh and dry biomass, seed dry weight per panicle, 1000-seed weight, and dry seed production. The optimal seed production for “Samurai Two” occurred at 90 DAP during the rainy season. Conversely, harvesting at 95 DAP significantly increased straw biomass's total fresh and dry weight, with this age being optimal for straw biomass production.